Asia Pacific in the Age of Globalization - Johnson, R.; Johnson, R. (Palgrave Macmillan Transnational History Series,, 2015)
The essays in this volume examine United States-East Asian relations in the framework of global history, incorporating fresh insights that have been offered by scholars on such topics as globalization, human rights, historical memory, and trans-cultural relations.